2014
DOI: 10.1155/2014/939163
|View full text |Cite
|
Sign up to set email alerts
|

The Tarsal Bone Test: A Basic Test of Health Sciences Students' Knowledge of Lower Limb Anatomy

Abstract: Objectives. The aim of the present study was to design an easy-to-use tool, the tarsal bone test (TBT), to provide a snapshot of podiatry students' basic anatomical knowledge of the bones of the lower limb. Methods. The study included 254 podiatry students from three different universities, 145 of them were first-year students and 109 were in their fourth and final years. The TBT was administered without prior notice to the participants and was to be completed in 5 minutes. Results. The results show that 97.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In contrast, in the test of first and fourth year podiatry students from three Spanish universities (who were, appropriately, tested on the anatomy of tarsal, rather than carpal bones) there was no significant difference in performance between the two generations [10]. In a similar study utilising the carpal bones test, fifth year chiropractic students at Australia's Murdoch University performed better than their second year counterparts, who had just finished their anatomy course [11].…”
Section: Number Of Bones Medical Chiropractic Medical 1st Year Physiomentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, in the test of first and fourth year podiatry students from three Spanish universities (who were, appropriately, tested on the anatomy of tarsal, rather than carpal bones) there was no significant difference in performance between the two generations [10]. In a similar study utilising the carpal bones test, fifth year chiropractic students at Australia's Murdoch University performed better than their second year counterparts, who had just finished their anatomy course [11].…”
Section: Number Of Bones Medical Chiropractic Medical 1st Year Physiomentioning
confidence: 90%
“…This "carpal bone test" and different versions of it has already been utilised in a number of studies to provide an initial estimate of the level of knowledge and retention rate in anatomy among the students and recent graduates in a number of health disciplines [7][8][9][10][11].…”
Section: Introduction Environmental Interactionsmentioning
confidence: 99%
“…17 To such end, several tools have been designed (ie, anatomy spot tests) like the carpal bone test 19 and the tarsal bone test. 20 These tests may help to provide a preliminary assessment of bone anatomy knowledge among health care professionals providing care for upper and lower extremity musculoskeletal conditions. 20 Previous research shows that medical students report a below-average level of confidence in the region-specific clinical examination of the musculoskeletal system 21 and that they exhibit worse retention of carpal bones anatomy than physical therapy students.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a cross-sectional study on the retention of anatomical knowledge among preclinical (second-year) and clinical (fifth-year) chiropractic students showed that the fifth-year students performed better than the second-year students. (5) Castillo-López et al (6) conducted a study using the tarsal bone test among the podiatry students and the most of the students identified the bones correctly. There was no significant difference in performance of the first and fourth-year students.…”
Section: Methodsmentioning
confidence: 99%
“…Health science subjects including anatomy are integrated with clinical skills for better clinical reasoning. (6) Retention of anatomical knowledge is not only to be pointed for and the preparation from the educators' aspectis also needed to be updated in such a way that the contents and mode of delivery should meet the needs of a modern medical and health science professional world. (7) Thus, this review was aimed to evaluate the anatomical knowledge among the medical, dental and health science professionals and their perceptions on application of anatomical knowledge in clinical practice.…”
Section: Introductionmentioning
confidence: 99%